Pelaksanaan Yoga Anak untuk Menstimulasi Motorik Kasar di TK Kristen Pniel Terpadu - Ana Sulisnani; Hapsari Windayanti; Diana Rosanti; Lailatul Farihah; Rosita Sekar Tanjung (Universitas Ngudi Waluyo, 2022)
From kindergarten education children learn to grow , get to know and memorize something from the activities applied, one of which is to play while learning. Growth and development is a process experienced by individuals from fetus to adulthood. Yoga or meditation is an alternative way that can improve children's knowledge and skills so that children can get good growth and development. The purpose of community service is to introduce children's yoga to the community, especially in integrated Pniel Christian Kindergarten which has never applied children's yoga because they think that yoga movements are the same as gymnastics movements. The respondents who participated in this study were 19 children and children aged 4-6 years from Semarang Regency. The implementation of the study used the method of providing education and training for children's yoga. The media used to display images for the delivery of material and live demonstrations for children's yoga training. The implementation of the research consists of pretest, material delivery, discussion, and posttest. Respondents were actively involved and had high enthusiasm during the implementation. Based on the results of community service, it can be concluded that there is an increase in knowledge and skills of yoga poses in children after being given health education using poster media and direct image display. AbstrakPada pendidikan TK anak-anak belajar untuk tumbuh , mengenal dan menghafal sesuatu dari kegiatan yang diterapkan, salah satunya adalah bermain sambil belajar. Tumbuh kembang merupakan suatu proses yang dialami oleh individu dari janin hingga dewasa. Yoga atau meditasi merupakan suatu cara alternatif yang dapat meningkatkan pengetahuan dan ketrampilan anak sehingga anak dapat memperoleh tumbuh kembang yang baik. Tujuan pengabdian kepada masyarakat adalah untuk memperkenalkan yoga anak kepada masyarakat terutama pada TK Kristen Pniel Terpadu yang belum pernah menerapkan yoga anak karena beranggapan bahwa gerakan yoga sama halnya seperti gerakan senam. Responden yang berpartisipasi dalam penelitian ini adalah 19 anak dan anak usia 4–6 tahun yang berasal dari Kabupaten Semarang. Pelaksanaan penelitian menggunakan metode pemberian pendidikan dan pelatihan yoga anak. Media yang digunakan tampilan gambar untuk penyampaian materi dan peragaan secara langsung untuk pelatihan yoga anak. Pelaksanaan penelitian terdiri dari pretest, penyampaian materi, diskusi, dan posttest. Berdasarkan hasil pengabdian kepada masyarakat dapat disimpulkan bahwa terjadi peningkatan motoric halus dan ketrampilan pose yoga pada anak setelah diberikan pendidikan kesehatan menggunakan media poster dan tampilan gambar secara langsung.